Assessing Postsurgical Outcomes with Prepectoral Breast Reconstruction: A Literature Review and Meta-analysis Update - Abhishek Chatterjee, MD, MBA (Wolters Kluwer, 2021)
Background:. Prepectoral implant-based breast reconstruction is an alternative to subpectoral/dual-plane reconstruction. Methods:. This study examined outcomes of prepectoral reconstruction using a meta-analysis of data pooled with data from our previous review. Thirty studies were included. Results:. Explantation, seroma, and infection were the most common complications with no animation deformity reported. Significantly lower odds of infection were observed with prepectoral compared with dual-plane reconstruction. Conclusions:. Current literature suggests that prepectoral reconstruction may be associated with lower rates of postsurgical infections.